Pengaruh Perilaku Organisasi dan Motivasi Kerja terhadap Kinerja Karyawan pada Perusahaan PT. Sentosa Harmony Steel di Cikande Serang Banten - Vera Maria; Gita Salwa Fauziah; Amanda Olivia; Astuti Ramayati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research focuses on examining the impact of organizational behavior and work motivation on the performance of employees at PT. Sentosa Harmony Steel Cikande. A quantitative methodology was utilized, employing a survey approach to gather data through questionnaires distributed among the employees of PT. Sentosa Harmony Steel. The analysis revealed that both organizational behavior and work motivation significantly contribute to enhancing employee performance. These results imply that a positive work environment, robust managerial support, and strong motivational factors can lead to increased productivity and success among employees. The study suggests that the company should consistently promote positive organizational behavior and adopt strategies to boost work motivation to achieve optimal performance.